2012
DOI: 10.1016/j.ophtha.2011.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Interim Results from the International Trial of Second Sight's Visual Prosthesis

Abstract: Purpose This study evaluates the Argus™ II Retinal Prosthesis System in blind subjects with severe outer retinal degeneration. Design The study design is a single arm, prospective, multicenter clinical trial. Participants Thirty subjects were enrolled in the United States and Europe between 6 June 2007 and 11 August 2009. All subjects were followed for a minimum of six months and up to 2.7 years. Methods The electronic stimulator and antenna of the implant was sutured onto the sclera using an encircling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
672
0
20

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 638 publications
(702 citation statements)
references
References 26 publications
10
672
0
20
Order By: Relevance
“…3 In the absence of functional photoreceptors, electrical stimulation of these inner retinal neurons was shown to enable patients to recover some visual perception and even perform some reading tasks. 4 These results collectively demonstrated that RGCs remain able to transmit information to the brain in late-stage RP. 5 However, prosthetic approaches do not yet allow sufficient resolution for face recognition or locomotion in an unknown environment.…”
Section: Introductionmentioning
confidence: 65%
“…3 In the absence of functional photoreceptors, electrical stimulation of these inner retinal neurons was shown to enable patients to recover some visual perception and even perform some reading tasks. 4 These results collectively demonstrated that RGCs remain able to transmit information to the brain in late-stage RP. 5 However, prosthetic approaches do not yet allow sufficient resolution for face recognition or locomotion in an unknown environment.…”
Section: Introductionmentioning
confidence: 65%
“…There is no effective intervention, although several clinical trials are underway to either slow down or arrest the progression of the disease. [3][4][5][6][7] Progression in RP has traditionally been monitored in the past by assessing visual fields and full-field electroretinography. Although Goldmann visual field testing was the gold standard, more recently static perimetry using the Humphrey Field Analyzer (HFA) (programs 30-2 and 10-2) has been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Direct electrical stimulation of the surviving inner retina has proven to be successful in restoring useful vision (6)(7)(8). One approach employs surgically implanted photovoltaic or electrode arrays to stimulate retinal ganglion cells (RGCs) (8) or bipolar cells (BCs) (6,7) directly in the inner nuclear layer (INL) of the degenerated retina, and promising results in clinical trials have led to US Food and Drug Administration approval for the Argus II device (Second Sight Medical Products, Inc.) (8).…”
mentioning
confidence: 99%
“…One approach employs surgically implanted photovoltaic or electrode arrays to stimulate retinal ganglion cells (RGCs) (8) or bipolar cells (BCs) (6,7) directly in the inner nuclear layer (INL) of the degenerated retina, and promising results in clinical trials have led to US Food and Drug Administration approval for the Argus II device (Second Sight Medical Products, Inc.) (8). The electrical implants demonstrate that inner retinal neurons in blind patients can respond to appropriate stimulation and lead to a useful visual percept allowing simple navigation and object recognition.…”
mentioning
confidence: 99%